1997
DOI: 10.1108/09684879710156478
|View full text |Cite
|
Sign up to set email alerts
|

Working and learning with electronic performance support systems: an effectiveness study

Abstract: In this study the effectiveness of electronic performance support systems (EPSS) is reported. Some of the expected advantages of EPSS, such as an increase in productivity and improved learning are evaluated with insurance agents using laptop computers. Theoretical statements, research design and hypotheses are presented. The conclusion is that EPSS was cheaper than classroom training and had some benefits for learners, but did not produce the expected benefit of an increase in productivity.processes are potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The collection of cost/benefit data should be collected not only from the proposed case studies, but from secondary data, such as practitioner publications and the Internet. For instance, Desmarais, Leclair, Fiset, and Talbi (1997) and Bastiaens et al (1997) present a cost-benefit analysis on electronic PSS, and other case studies can be found on the Internet through the EPSS library (1997). As another example, Geisman (1991) conducted a cost/benefit analysis of classroom-based instruction and computer-based tutorials in one organization.…”
Section: Suggested Research Methodologiesmentioning
confidence: 98%
“…The collection of cost/benefit data should be collected not only from the proposed case studies, but from secondary data, such as practitioner publications and the Internet. For instance, Desmarais, Leclair, Fiset, and Talbi (1997) and Bastiaens et al (1997) present a cost-benefit analysis on electronic PSS, and other case studies can be found on the Internet through the EPSS library (1997). As another example, Geisman (1991) conducted a cost/benefit analysis of classroom-based instruction and computer-based tutorials in one organization.…”
Section: Suggested Research Methodologiesmentioning
confidence: 98%
“…The original definitions of performance support focused on performance enhancement (Bastiaens, Nijhof, Streumer, & Abma, 1997 ;Gery, 2002 ). Rosenberg ( 1995 ) claimed that performance support ' s greatest potential is associated with its unique ability to solve business rather than educational, problems.…”
Section: The Effectiveness Of Performance Support As a Performance Enmentioning
confidence: 99%
“…Two previous studies that attempted to validate this assumption produced conflicting results. Bastiaens, Nijhof, Streumer, and Abma (1997) explored the effectiveness of combinations of computer-based and paper-based performance support with computer-based and instructorled training. The researchers conducted a study with insurance agents and found that they preferred the paper-based forms over the electronic software tool as well as the instructor-led training over computer-based training.…”
Section: Epss and Training As Performance Interventionsmentioning
confidence: 99%